Sorption of metals and metalloids in hydraulic fracturing flowback water to surficial sediments - Sean P. Funk; Katherine N. Snihur; Konstantin von Gunten; Logan Swaren; Greg G. Goss; Daniel S. Alessi (Applied Geochemistry, 2026)

Exposome-wide associations and polyexposure risks of workplace chemical exposures on adult asthma: The Personalized Environment and Genes Study (PEGS) - Yujing Chen; Farida S. Akhtari; Yixuan He; Lihang Yu; Vy Kim Nguyen; Martin Tsz-Ki Tsui; Yuki Mizuno; William E. Funk; Crystal Ying Chan; Lap Ah Tse; Kin Fai Ho; Chirag J. Patel; et al. (Environmental Research, 2025)

Population Genomics Reveals Local Adaptation Related to Temperature Variation in Two Stream Frog Species: Implications for Vulnerability to Climate Warming - Brenna R. Forester; Amanda S. Cicchino; Alisha A. Shah; Austin B. Mudd; Eric C. Anderson; Jessen V. Bredeson; Andrew J. Crawford; Jason B. Dunham; Cameron K. Ghalambor; Erin L. Landguth; Brent W. Murray; Daniel Rokhsar; et al. (Molecular Ecology, 2025)
Identifying populations at highest risk from climate change is a critical component of conservation efforts. However, vulnerability assessments are usually applied at the species level, even though intraspecific variation in exposure, sensitivity and adaptive capacity play a crucial role in determining vulnerability. Genomic data can inform intraspecific vulnerability by identifying signatures of local adaptation that reflect population‐level variation in sensitivity and adaptive capacity. Here, we address the question of local adaptation to temperature and the genetic basis of thermal tolerance in two stream frogs ( Ascaphus truei and A. montanus ). Building on previous physiological and temperature data, we used whole‐genome resequencing of tadpoles from four sites spanning temperature gradients in each species to test for signatures of local adaptation. To support these analyses, we developed the first annotated reference genome for A. truei . We then expanded the geographic scope of our analysis using targeted capture at an additional 11 sites per species. We found evidence of local adaptation to temperature based on physiological and genomic data in A. montanus and genomic data in A. truei , suggesting similar levels of sensitivity (i.e., susceptibility) among populations regardless of stream temperature. However, invariant thermal tolerances across temperatures in A. truei suggest that populations occupying warmer streams may be most sensitive. We identified high levels of evolutionary potential in both species based on genomic and physiological data. While further integration of these data is needed to comprehensively evaluate spatial variation in vulnerability, this work illustrates the value of genomics in identifying spatial patterns of climate change vulnerability.

Annual Temperature Range Drives Thermal Breadth of Freshwater Insects Across Multiple Spatial Scales - Beatrice S. Dewenter; Darren P. Giling; Alisha A. Shah; Jane Hughes; N. LeRoy Poff; Cameron K. Ghalambor; W. Chris Funk; Stephanie Bristow; Ross M. Thompson; Ben J. Kefford (Ecology Letters, 2025)
Thermal breadth ( T br ) is a critical trait influencing organisms' response to climate change. Three hypotheses seek to explain interspecific and interpopulation variation in T br , each relying on a different temperature driver: Climate Variability Hypothesis (CVH)–annual temperature range; Thermal Constraints Hypothesis (TCH)–mean annual temperature; and Diel Narrowing Hypothesis (DNH)–mean diel temperature range. We test these hypotheses by measuring the T br of freshwater insects (Ephemeroptera, Plecoptera and Trichoptera) along elevational gradients in the Americas and Australia, contrasting warm and cool adapted species from low climate variability tropical regions and high climate variability temperate regions. We find strong and consistent support for the CVH, limited support for the TCH (in two of four regions) and no support for the DNH. We conclude that T br of freshwater insects is better explained by annual temperature variability, rather than high temperatures or diel temperature variability.

P18-72 Integration of Metabolomics and Transcriptomics, as well as Mitostress, CALUX Assays and Targeted Proteomics for an Improved Mechanism-based Hazard Characterization of Drug-induced Liver Injury - F. Zickgraf; L. Wijaya; T. de Boer; C. Budin; S. Moco; V. Pozo Garcia; O. Pötz; P. Ternes; V. Giri; B. van de Water; C. Gomes; H. Kamp; et al. (Toxicology Letters, 2025)

P18-103 Historical control database and acceptance criteria for a comparative in vitro hepatic enzyme assay(KaLy-Cell method) - S. Kellum; K. Choudhury; S. Melching-Kollmuss; A. Schafer; C. Parmentier; X. Sopko; L. Richert; H. Tinwell; C. Walter; I. Wohlman; F. Zhang; S. Catalano; et al. (Toxicology Letters, 2025)

Correction: DNA-based studies and genetic diversity indicator assessments are complementary approaches to conserving evolutionary potential - Sean Hoban; Ivan Paz-Vinas; Robyn E. Shaw; Luis Castillo-Reina; Jessica M. da Silva; J. Andrew Dewoody; Robert Ekblom; Ancuta Fedorca; Brenna R. Forester; W. Chris Funk; Julia C. Geue; Myriam Heuertz; et al. (Conservation Genetics, 2024)

DNA-based studies and genetic diversity indicator assessments are complementary approaches to conserving evolutionary potential - Sean Hoban; Ivan Paz-Vinas; Robyn E. Shaw; Luis Castillo-Reina; Jessica M. da Silva; J. Andrew DeWoody; Robert Ekblom; Ancuta Fedorca; Brenna R. Forester; W. Chris Funk; Julia C. Geue; Myriam Heuertz; et al. (Conservation Genetics, 2024)
Genetic diversity is essential for maintaining healthy populations and ecosystems. Several approaches have recently been developed to evaluate population genetic trends without necessarily collecting new genetic data. Such “genetic diversity indicators” enable rapid, large-scale evaluation across dozens to thousands of species. Empirical genetic studies, when available, provide detailed information that is important for management, such as estimates of gene flow, inbreeding, genetic erosion and adaptation. In this article, we argue that the development and advancement of genetic diversity indicators is a complementary approach to genetic studies in conservation biology, but not a substitute. Genetic diversity indicators and empirical genetic data can provide different information for conserving genetic diversity. Genetic diversity indicators enable affordable tracking, reporting, prioritization and communication, although, being proxies, do not provide comprehensive evaluation of the genetic status of a species. Conversely, genetic methods offer detailed analysis of the genetic status of a given species or population, although they remain challenging to implement for most species globally, given current capacity and resourcing. We conclude that indicators and genetic studies are both important for genetic conservation actions and recommend they be used in combination for conserving and monitoring genetic diversity.

P20-05 Polymer REACh on the horizon: technical challenges with polymer materials in several OECD test guideline methods addressing effects on human health and on biotic systems - S.N. Kolle; P. Demuth; N. Hambruch; N. Honarvar; S. Lüderwald; D. Funk-Weyer; R. Landsiedel (Toxicology Letters, 2024)

P09-12 Thyroid hormones concentrations in cerebellum, cortex and whole-brain rat samples at certain life stages - C. Hindrichs; T. Walk; S. Melching-Kollmuss; R. Landsiedel; S. Schneider; H. Kamp; D. Funk-Weyer (Toxicology Letters, 2024)

P06-23 Integration of metabolomics and transcriptomics for improved mechanism-based hazard characterization of drug-induced liver injury - F.M. Zickgraf; L. Wijaya; T. de Boer; C. Budin; S. Moco; V. Pozo Garcia; P. Ternes; V. Giri; C. Gomes; B. van de Water; H. Kamp; D. Funk-Weyer (Toxicology Letters, 2024)

Conservation genomics of an endangered montane amphibian reveals low population structure, low genomic diversity and selection pressure from disease - D. R. Trumbo; B. M. Hardy; H. J. Crockett; E. Muths; B. R. Forester; R. G. Cheek; S. J. Zimmerman; S. Corey‐Rivas; L. L. Bailey; W. C. Funk (Molecular Ecology, 2023)
Wildlife diseases are a major global threat to biodiversity. Boreal toads ( Anaxyrus [Bufo] boreas ) are a state‐endangered species in the southern Rocky Mountains of Colorado and New Mexico, and a species of concern in Wyoming, largely due to lethal skin infections caused by the amphibian chytrid fungus Batrachochytrium dendrobatidis ( Bd ). We performed conservation and landscape genomic analyses using single nucleotide polymorphisms from double‐digest, restriction site‐associated DNA sequencing in combination with the development of the first boreal toad (and first North American toad) reference genome to investigate population structure, genomic diversity, landscape connectivity and adaptive divergence. Genomic diversity ( π = 0.00034–0.00040) and effective population sizes ( N e = 8.9–38.4) were low, likely due to post‐Pleistocene founder effects and Bd ‐related population crashes over the last three decades. Population structure was also low, likely due to formerly high connectivity among a higher density of geographically proximate populations. Boreal toad gene flow was facilitated by low precipitation, cold minimum temperatures, less tree canopy, low heat load and less urbanization. We found >8X more putatively adaptive loci related to Bd intensity than to all other environmental factors combined, and evidence for genes under selection related to immune response, heart development and regulation and skin function. These data suggest boreal toads in habitats with Bd have experienced stronger selection pressure from disease than from other, broad‐scale environmental variations. These findings can be used by managers to conserve and recover the species through actions including reintroduction and supplementation of populations that have declined due to Bd .

P22-44: In vitro – in vivo comparison of read-across approaches for phenoxy herbicides based on metabolome data from rat plasma and HepG2 cells - G. Caroline; F.M. Zickgraf; V. Giri; V. Haake; B. Birk; S. Sperber; H.-A. Huener; A. Verlohner; P. Driemert; T. Walk; D. Funk-Weyer; H. Kamp (Toxicology Letters, 2023)

P08-13: Analysis of Thyroid Hormone Metabolites in Rat Brain using an automated online-SPE-LC-MS/MS method - C. Hindrichs; T. Walk; S. Melching-Kollmuss; R. Landsiedel; H. Kamp; D. Funk-Weyer (Toxicology Letters, 2023)

Symbiotic nitrogen fixation strategies relate to phenotypic plasticity but not invasion risk - Angalee S. Kirby; Rebecca Ostertag; Duncan N. L. Menge; Jennifer L. Funk (Biological Invasions, 2023)

Genetic diversity goals and targets have improved, but remain insufficient for clear implementation of the post-2020 global biodiversity framework - Sean Hoban; Michael W. Bruford; Jessica M. da Silva; W. Chris Funk; Richard Frankham; Michael J. Gill; Catherine E. Grueber; Myriam Heuertz; Margaret E. Hunter; Francine Kershaw; Robert C. Lacy; Caroline Lees; et al. (Conservation Genetics, 2023)
Genetic diversity among and within populations of all species is necessary for people and nature to survive and thrive in a changing world. Over the past three years, commitments for conserving genetic diversity have become more ambitious and specific under the Convention on Biological Diversity’s (CBD) draft post-2020 global biodiversity framework (GBF). This Perspective article comments on how goals and targets of the GBF have evolved, the improvements that are still needed, lessons learned from this process, and connections between goals and targets and the actions and reporting that will be needed to maintain, protect, manage and monitor genetic diversity. It is possible and necessary that the GBF strives to maintain genetic diversity within and among populations of all species, to restore genetic connectivity, and to develop national genetic conservation strategies, and to report on these using proposed, feasible indicators.

Symbiotic nitrogen fixation does not stimulate soil phosphatase activity under temperate and tropical trees - Emily A. Jager; Andrew W. Quebbeman; Amelia A. Wolf; Steven S. Perakis; Jennifer L. Funk; Duncan N. L. Menge (Oecologia, 2023)

A metabolomic signature of the APOE2 allele - Paola Sebastiani; Zeyuan Song; Dylan Ellis; Qu Tian; Michaela Schwaiger-Haber; Ethan Stancliffe; Michael S. Lustgarten; Cory C. Funk; Priyanka Baloni; Cong-Hui Yao; Shakchhi Joshi; Megan M. Marron; et al. (GeroScience, 2023)

Consensus Head Acceleration Measurement Practices (CHAMP): Origins, Methods, Transparency and Disclosure - Kristy B. Arbogast; Jaclyn B. Caccese; Thomas A. Buckley; Andrew S. McIntosh; Kyvory Henderson; Brian D. Stemper; Gary Solomon; Steven P. Broglio; James R. Funk; Jeff R. Crandall (Annals of Biomedical Engineering, 2022)
The use of head kinematic measurement devices has recently proliferated owing to technology advances that make such measurement more feasible. In parallel, demand to understand the biomechanics of head impacts and injury in sports and the military has increased as the burden of such loading on the brain has received focused attention. As a result, the field has matured to the point of needing methodological guidelines to improve the rigor and consistency of research and reduce the risk of scientific bias. To this end, a diverse group of scientists undertook a comprehensive effort to define current best practices in head kinematic measurement, culminating in a series of manuscripts outlining consensus methodologies and companion summary statements. Summary statements were discussed, revised, and voted upon at the Consensus Head Acceleration Measurement Practices (CHAMP) Conference in March 2022. This manuscript summarizes the motivation and methods of the consensus process and introduces recommended reporting checklists to be used to increase transparency and rigor of future experimental design and publication of work in this field. The checklists provide an accessible means for researchers to apply the best practices summarized in the companion manuscripts when reporting studies utilizing head kinematic measurement in sport and military settings.

Best Practices for Conducting Physical Reconstructions of Head Impacts in Sport - James R. Funk; Andrew S. McIntosh; Chris Withnall; Michael Wonnacott; Ron Jadischke (Annals of Biomedical Engineering, 2022)

Genomics‐informed delineation of conservation units in a desert amphibian - Brenna R. Forester; Melanie Murphy; Chad Mellison; Jeffrey Petersen; David S. Pilliod; Rachel Van Horne; Jim Harvey; W. Chris Funk (Molecular Ecology, 2022)
Delineating conservation units (CUs, e.g., evolutionarily significant units, ESUs, and management units, MUs) is critical to the recovery of declining species because CUs inform both listing status and management actions. Genomic data have strengths and limitations in informing CU delineation and related management questions in natural systems. We illustrate the value of using genomic data in combination with landscape, dispersal and occupancy data to inform CU delineation in Nevada populations of the Great Basin Distinct Population Segment of the Columbia spotted frog ( Rana luteiventris ). R. luteiventris occupies naturally fragmented aquatic habitats in this xeric region, but beaver removal, climate change and other factors have put many of these populations at high risk of extirpation without management intervention. We addressed three objectives: (i) assessing support for ESUs within Nevada; (ii) evaluating and revising, if warranted, the current delineation of MUs; and (iii) evaluating genetic diversity, effective population size, adaptive differentiation and functional connectivity to inform ongoing management actions. We found little support for ESUs within Nevada but did identify potential revisions to MUs based on unique landscape drivers of connectivity that distinguish these desert populations from those in the northern portion of the species range. Effective sizes were uniformly small, with low genetic diversity and weak signatures of adaptive differentiation. Our findings suggest that management actions, including translocations and genetic rescue, might be warranted. Our study illustrates how a carefully planned genetic study, designed to address priority management goals that include CU delineation, can provide multiple insights to inform conservation action.

Impacts of drought and native grass competition on buffelgrass (Pennisetum ciliare) - Hannah L. Farrell; Jennifer Funk; Darin Law; Elise S. Gornish (Biological Invasions, 2022)

Parasites as conservation tools - Roderick B. Gagne; Kevin R. Crooks; Meggan E. Craft; Elliott S. Chiu; Nicholas M. Fountain‐Jones; Jennifer L. Malmberg; Scott Carver; W. Chris Funk; Sue VandeWoude (Conservation Biology, 2022)
Parasite success typically depends on a close relationship with one or more hosts; therefore, attributes of parasitic infection have the potential to provide indirect details of host natural history and are biologically relevant to animal conservation. Characterization of parasite infections has been useful in delineating host populations and has served as a proxy for assessment of environmental quality. In other cases, the utility of parasites is just being explored, for example, as indicators of host connectivity. Innovative studies of parasite biology can provide information to manage major conservation threats by using parasite assemblage, prevalence, or genetic data to provide insights into the host. Overexploitation, habitat loss and fragmentation, invasive species, and climate change are major threats to animal conservation, and all of these can be informed by parasites.

A unifying framework for analyzing temporal changes in functional and taxonomic diversity along disturbance gradients - Erin I. Larson; N. LeRoy Poff; W. Chris Funk; Rachel A. Harrington; Boris C. Kondratieff; Scott G. Morton; Alexander S. Flecker (Ecology, 2021)
Frameworks exclusively considering functional diversity are gaining popularity, as they complement and extend the information provided by taxonomic diversity metrics, particularly in response to disturbance. Taxonomic diversity should be included in functional diversity frameworks to uncover the functional mechanisms causing species loss following disturbance events. We present and test a predictive framework that considers temporal functional and taxonomic diversity responses along disturbance gradients. Our proposed framework allows us to test different multidimensional metrics of taxonomic diversity that can be directly compared to calculated multidimensional functional diversity metrics. It builds on existing functional diversity–disturbance frameworks both by using a gradient approach and by jointly considering taxonomic and functional diversity. We used previously unpublished stream insect community data collected prior to, and for the two years following, an extreme flood event that occurred in 2013. Using 14 northern Colorado mountain streams, we tested our framework and determined that taxonomic diversity metrics calculated using multidimensional methods resulted in concordance between taxonomic and functional diversity responses. By considering functional and taxonomic diversity together and using a gradient approach, we were able to identify some of the mechanisms driving species losses following this extreme disturbance event.

Laboratory Evaluation of Shell Add-On Products for American Football Helmets for Professional Linemen - Ann M. Bailey; James R. Funk; Jeff R. Crandall; Barry S. Myers; Kristy B. Arbogast (Annals of Biomedical Engineering, 2021)

A nucleobase cation symporter 2, EaXanP, from Erwinia amylovora transports xanthine - Andrea M. Funk; Regan B. Huntley; George S. Mourad; Neil P. Schultes (Journal of Plant Pathology, 2021)

N supply mediates the radiative balance of N 2 O emissions and CO 2 sequestration driven by N‐fixing vs. non‐fixing trees - Sian Kou‐Giesbrecht; Jennifer L. Funk; Steven S. Perakis; Amelia A. Wolf; Duncan N. L. Menge (Ecology, 2021)
Forests are a significant CO 2 sink. However, CO 2 sequestration in forests is radiatively offset by emissions of nitrous oxide (N 2 O), a potent greenhouse gas, from forest soils. Reforestation, an important strategy for mitigating climate change, has focused on maximizing CO 2 sequestration in plant biomass without integrating N 2 O emissions from soils. Although nitrogen (N)‐fixing trees are often recommended for reforestation because of their rapid growth on N‐poor soil, they can stimulate significant N 2 O emissions from soils. Here, we first used a field experiment to show that a N‐fixing tree ( Robinia pseudoacacia ) initially mitigated climate change more than a non‐fixing tree ( Betula nigra ). We then used our field data to parameterize a theoretical model to investigate these effects over time. Under lower N supply, N‐fixers continued to mitigate climate change more than non‐fixers by overcoming N limitation of plant growth. However, under higher N supply, N‐fixers ultimately mitigated climate change less than non‐fixers by enriching soil N and stimulating N 2 O emissions from soils. These results have implications for reforestation, suggesting that N‐fixing trees are more effective at mitigating climate change at lower N supply, whereas non‐fixing trees are more effective at mitigating climate change at higher N supply.

Using seasonal rainfall clusters to explain the interannual variability of the rain belt over the Greater Horn of Africa - Larisa S. Seregina; Andreas H. Fink; Roderick van der Linden; Chris Funk; Joaquim G. Pinto (International Journal of Climatology, 2021)
The seasonal cycle of rainfall over the Greater Horn of Africa (GHA) is dominated by the latitudinal migration and activity of the tropical rain belt (TRB). The TRB exhibits high interannual variability in the GHA and the reasons for the recent dry period in the Long Rains (March–May) are poorly understood. In addition, few studies have addressed the rainfall fluctuations during the Msimu Rains (Dec.–Mar.) in the southern GHA region. Interannual variations of the seasonal cycle of the TRB between 1981 and 2018 were analysed using two statistical indices. The Rainfall Cluster Index (RCI) describes the seasonal cycle as a succession of six characteristic rainfall patterns, while the Seasonal Location Index (SLI) captures the latitudinal location of the TRB. The SLI and RCI depict the full seasonal cycle of the TRB supporting interpretations of the interannual variations and trends. The Msimu Rains are dominated by two clusters with opposite rainfall characteristics between the Congo Basin and Tanzania. The associated anomalies in moisture flux and divergence indicate variations in the location of the TRB originating from an interplay between low‐level air flows from the Atlantic and Indian Oceans and tropical and subtropical teleconnections. The peak period of the Long Rains shows a complex composition of five clusters, which is tightly connected to intraseasonal and interannual variability of latitudinal locations of the TRB. A persistent location of the TRB near the equator, evidenced in a frequent occurrence of a cluster related to an anomalously weak Walker circulation, is associated with wet conditions over East Africa. Dry Long Rains are associated with strong and frequent latitudinal variations of the TRB position with a late onset and intermittent rainfall. These results offer new opportunities to understand recent variability and trends in the GHA region.

Temperature dependence of metabolic rate in tropical and temperate aquatic insects: Support for the Climate Variability Hypothesis in mayflies but not stoneflies - Alisha A. Shah; H. Arthur Woods; Justin C. Havird; Andrea C. Encalada; Alexander S. Flecker; W. Chris Funk; Juan M. Guayasamin; Boris C. Kondratieff; N. LeRoy Poff; Steven A. Thomas; Kelly R. Zamudio; Cameron K. Ghalambor (Global Change Biology, 2021)
A fundamental gap in climate change vulnerability research is an understanding of the relative thermal sensitivity of ectotherms. Aquatic insects are vital to stream ecosystem function and biodiversity but insufficiently studied with respect to their thermal physiology. With global temperatures rising at an unprecedented rate, it is imperative that we know how aquatic insects respond to increasing temperature and whether these responses vary among taxa, latitudes, and elevations. We evaluated the thermal sensitivity of standard metabolic rate in stream‐dwelling baetid mayflies and perlid stoneflies across a ~2,000 m elevation gradient in the temperate Rocky Mountains in Colorado, USA, and the tropical Andes in Napo, Ecuador. We used temperature‐controlled water baths and microrespirometry to estimate changes in oxygen consumption. Tropical mayflies generally exhibited greater thermal sensitivity in metabolism compared to temperate mayflies; tropical mayfly metabolic rates increased more rapidly with temperature and the insects more frequently exhibited behavioral signs of thermal stress. By contrast, temperate and tropical stoneflies did not clearly differ. Varied responses to temperature among baetid mayflies and perlid stoneflies may reflect differences in evolutionary history or ecological roles as herbivores and predators, respectively. Our results show that there is physiological variation across elevations and species and that low‐elevation tropical mayflies may be especially imperiled by climate warming. Given such variation among species, broad generalizations about the vulnerability of tropical ectotherms should be made more cautiously.

Position-Specific Circumstances of Concussions in the NFL: Toward the Development of Position-Specific Helmets - David J. Lessley; Richard W. Kent; Joseph M. Cormier; Christopher P. Sherwood; James R. Funk; Jeff R. Crandall; Barry S. Myers; Kristy B. Arbogast (Annals of Biomedical Engineering, 2020)

Development and Evaluation of a Test Method for Assessing the Performance of American Football Helmets - Ann M. Bailey; Erin J. Sanchez; Gwansik Park; Lee F. Gabler; James R. Funk; Jeff R. Crandall; Michael Wonnacott; Chris Withnall; Barry S. Myers; Kristy B. Arbogast (Annals of Biomedical Engineering, 2020)

Comparison of Laboratory and On-Field Performance of American Football Helmets - Ann M. Bailey; Timothy L. McMurry; Joseph M. Cormier; James R. Funk; Jeff R. Crandall; Christina D. Mack; Barry S. Myers; Kristy B. Arbogast (Annals of Biomedical Engineering, 2020)

Keys to enhancing the value of invasion ecology research for management - Jennifer L. Funk; Ingrid M. Parker; Virginia Matzek; S. Luke Flory; Erik T. Aschehoug; Carla M. D’Antonio; Wayne Dawson; Diane M. Thomson; Justin Valliere (Biological Invasions, 2020)

Disparities in the use of stereotactic radiosurgery for the treatment of lung cancer brain metastases: a SEER-Medicare study - Mustafa S. Ascha; Kaitlyn Funk; Andrew E. Sloan; Carol Kruchko; Jill S. Barnholtz-Sloan (Clinical & Experimental Metastasis, 2020)

A search for new sources below 100 MeV in the Fermi-LAT data - G. Principe; D. Malyshev; J. Ballet; S. Funk (Rendiconti Lincei. Scienze Fisiche e Naturali, 2019)

Regional variation in drivers of connectivity for two frog species ( Rana pretiosa and R. luteiventris ) from the U.S. Pacific Northwest - Jeanne M. Robertson; Melanie A. Murphy; Christopher A. Pearl; Michael J. Adams; Mónica I. Páez‐Vacas; Susan M. Haig; David S. Pilliod; Andrew Storfer; W. Chris Funk (Molecular Ecology, 2018)
Comparative landscape genetics has uncovered high levels of variability in which landscape factors affect connectivity among species and regions. However, the relative importance of species traits versus environmental variation for predicting landscape patterns of connectivity is unresolved. We provide evidence from a landscape genetics study of two sister taxa of frogs, the Oregon spotted frog ( Rana pretiosa ) and the Columbia spotted frog ( Rana luteiventris ) in Oregon and Idaho, USA . Rana pretiosa is relatively more dependent on moisture for dispersal than R. luteiventris , so if species traits influence connectivity, we predicted that connectivity among R. pretiosa populations would be more positively associated with moisture than R. luteiventris . However, if environmental differences are important drivers of gene flow, we predicted that connectivity would be more positively related to moisture in arid regions. We tested these predictions using eight microsatellite loci and gravity models in two R. pretiosa regions and four R. luteiventris regions ( n = 1,168 frogs). In R. pretiosa , but not R. luteiventris , connectivity was positively related to mean annual precipitation, supporting our first prediction. In contrast, connectivity was not more positively related to moisture in more arid regions. Various temperature metrics were important predictors for both species and in all regions, but the directionality of their effects varied. Therefore, the pattern of variation in drivers of connectivity was consistent with predictions based on species traits rather than on environmental variation.

Extreme streams: species persistence and genomic change in montane insect populations across a flooding gradient - N. LeRoy Poff; Erin I. Larson; Patricia E. Salerno; Scott G. Morton; Boris C. Kondratieff; Alexander S. Flecker; Kelly R. Zamudio; W. Chris Funk (Ecology Letters, 2018)
The ecological and evolutionary consequences of extreme events are poorly understood. Here, we tested predictions about species persistence and population genomic change in aquatic insects in 14 Colorado mountain streams across a hydrological disturbance gradient caused by a one in 500‐year rainfall event. Taxa persistence ranged from 39 to 77% across sites and declined with increasing disturbance in relation to species' resistance and resilience traits. For taxa with mobile larvae and terrestrial adult stages present at the time of the flood, average persistence was 84% compared to 25% for immobile taxa that lacked terrestrial adults. For two of six species analysed, genomic diversity (allelic richness) declined after the event. For one species it greatly expanded, suggesting resilience via re‐colonisation from upstream populations. Thus, while resistance and resilience traits can explain species persistence to extreme disturbance, population genomic change varies among species, challenging generalisations about evolutionary responses to extreme events at landscape scales.

Urban landscapes can change virus gene flow and evolution in a fragmentation‐sensitive carnivore - Nicholas M. Fountain‐Jones; Meggan E. Craft; W. Chris Funk; Chris Kozakiewicz; Daryl R. Trumbo; Erin E. Boydston; Lisa M. Lyren; Kevin Crooks; Justin S. Lee; Sue VandeWoude; Scott Carver (Molecular Ecology, 2017)
Urban expansion has widespread impacts on wildlife species globally, including the transmission and emergence of infectious diseases. However, there is almost no information about how urban landscapes shape transmission dynamics in wildlife. Using an innovative phylodynamic approach combining host and pathogen molecular data with landscape characteristics and host traits, we untangle the complex factors that drive transmission networks of feline immunodeficiency virus (FIV) in bobcats ( Lynx rufus ). We found that the urban landscape played a significant role in shaping FIV transmission. Even though bobcats were often trapped within the urban matrix, FIV transmission events were more likely to occur in areas with more natural habitat elements. Urban fragmentation also resulted in lower rates of pathogen evolution, possibly owing to a narrower range of host genotypes in the fragmented area. Combined, our findings show that urban landscapes can have impacts on a pathogen and its evolution in a carnivore living in one of the most fragmented and urban systems in North America. The analytical approach used here can be broadly applied to other host–pathogen systems, including humans.

Dose–response relationship of temozolomide, determined by the Pig-a, comet, and micronucleus assay - M. Guérard; G. Johnson; S. Dertinger; G. Duran-Pacheco; J. Funk; A. Zeller (Archives of Toxicology, 2017)

Effects of prazosin and doxazosin on yohimbine-induced reinstatement of alcohol seeking in rats - D. Funk; K. Coen; S. Tamadon; Z. Li; A. Loughlin; A. D. Lê (Psychopharmacology, 2016)

Semiautomated quantitative image analysis of glomerular immunohistochemistry markers desmin, vimentin, podocin, synaptopodin and WT-1 in acute and chronic rat kidney disease models - J. Funk; V. Ott; A. Herrmann; W. Rapp; S. Raab; W. Riboulet; A. Vandjour; E. Hainaut; A. Benardeau; T. Singer; B. Jacobsen (Histochemistry and Cell Biology, 2016)

Lagged effects of early-season herbivores on valley oak fecundity - Ian S. Pearse; Kyle A. Funk; Thomas S. Kraft; Walter D. Koenig (Oecologia, 2015)

Burning characteristics of low-cost safety charcoal briquettes made from wood residues and soil for domestic use - M. Meincken; S. Funk (Agroforestry Systems, 2015)

Pollen limitation and flower abortion in a wind‐pollinated, masting tree - Ian S. Pearse; Walter D. Koenig; Kyle A. Funk; Mario B. Pesendorfer (Ecology, 2015)
Pollen limitation is a key assumption of theories that explain mast seeding, which is common among wind‐pollinated and woody plants. In particular, the pollen coupling hypothesis and pollination Moran effect hypothesis assume pollen limitation as a factor that synchronizes seed crops across individuals. The existence of pollen limitation has not, however, been unambiguously demonstrated in wind‐pollinated, masting trees. We conducted a two‐year pollen supplementation experiment on a masting oak species, Quercus lobata . Supplemental pollen increased acorn set in one year but not in the other, supporting the importance of pollen coupling and pollination Moran effect models of mast seeding. We also tracked the fate of female flowers over five years and found that the vast majority of flowers were aborted for reasons unrelated to pollination, even in the presence of excess pollen. Pollen limitation can reduce annual seed set in a wind‐pollinated tree, but factors other than pollen limitation cause the majority of flower abortion.

Locally adapted traits maintained in the face of high gene flow - S. W. Fitzpatrick; J. C. Gerberich; J. A. Kronenberger; L. M. Angeloni; W. C. Funk (Ecology Letters, 2015)
Gene flow between phenotypically divergent populations can disrupt local adaptation or, alternatively, may stimulate adaptive evolution by increasing genetic variation. We capitalised on historical Trinidadian guppy transplant experiments to test the phenotypic effects of increased gene flow caused by replicated introductions of adaptively divergent guppies, which were translocated from high‐ to low‐predation environments. We sampled two native populations prior to the onset of gene flow, six historic introduction sites, introduction sources and multiple downstream points in each basin. Extensive gene flow from introductions occurred in all streams, yet adaptive phenotypic divergence across a gradient in predation level was maintained. Descendants of guppies from a high‐predation source site showed high phenotypic similarity with native low‐predation guppies in as few as ~12 generations after gene flow, likely through a combination of adaptive evolution and phenotypic plasticity. Our results demonstrate that locally adapted phenotypes can be maintained despite extensive gene flow from divergent populations.

Water availability strongly impacts population genetic patterns of an imperiled Great Plains endemic fish - S. W. Fitzpatrick; H. Crockett; W. C. Funk (Conservation Genetics, 2014)

Dietary (periphyton) and aqueous Zn bioaccumulation dynamics in the mayfly Centroptilum triangulifer - K. S. Kim; D. H. Funk; D. B. Buchwalter (Ecotoxicology, 2012)

Population genetics of introduced bullfrogs, Rana (Lithobates) catesbeianus, in the Willamette Valley, Oregon, USA - W. Chris Funk; Tiffany S. Garcia; George A. Cortina; Rebbecca H. Hill (Biological Invasions, 2011)

In vitro metastatic colonization of human ovarian cancer cells to the omentum - Shaheena M. Khan; Holly M. Funk; Sophie Thiolloy; Tamara L. Lotan; Jonathan Hickson; Gail S. Prins; Angela F. Drew; Carrie W. Rinker-Schaeffer (Clinical & Experimental Metastasis, 2010)

Reorientation by slope cues in humans - Daniele Nardi; Amanda Y. Funk; Nora S. Newcombe; Thomas F. Shipley (Cognitive Processing, 2009)

MtDNA reveals strong genetic differentiation among geographically isolated populations of the golden brown mouse lemur, Microcebus ravelobensis - K. Guschanski; G. Olivieri; S. M. Funk; U. Radespiel (Conservation Genetics, 2007)

Molecular Phylogenetic Relationships Among Crested-tailed Mice (Genus Habromys) - Duke S. Rogers; Christopher C. Funk; Jacqueline R. Miller; Mark D. Engstrom (Journal of Mammalian Evolution, 2007)

Philopatry and reproductive success in Bornean orang‐utans ( Pongo pygmaeus ) - B. GOOSSENS; J. M. SETCHELL; S. S. JAMES; S. M. FUNK; L. CHIKHI; A. ABULANI; M. ANCRENAZ; I. LACKMAN‐ANCRENAZ; M. W. BRUFORD (Molecular Ecology, 2006)
Behavioural observations suggest that orang‐utans are semi‐solitary animals with females being philopatric and males roaming more widely in search of receptive partners, leading to the prediction that females are more closely related than males at any given site. In contrast, our study presents evidence for male and female philopatry in the orang‐utan. We examined patterns of relatedness and parentage in a wild orang‐utan population in Borneo using noninvasively collected DNA samples from animals observed to defecate, and microsatellite markers to assess dispersal and mating strategies. Surprisingly, resident females were equally as related to other resident females (mean r xy = 0.303) as resident males were to other resident males (mean r xy = 0.305). Moreover, resident females were more related to each other and to the resident males than they were to nonresident females, and resident males were more related to each other (and resident females) than they were to nonresident males. We assigned genetic mothers to 12 individuals in the population, while sires could be identified for eight. Both flanged males and unflanged males achieved paternity, similar to findings reported for Sumatran orang‐utans.

Effects of unconditioned and conditioned social defeat on alcohol self-administration and reinstatement of alcohol seeking in rats - D. Funk; S. Harding; W. Juzytsch; A. D. Lê (Psychopharmacology, 2005)

Role of alpha-2 adrenoceptors in stress-induced reinstatement of alcohol seeking and alcohol self-administration in rats - A. D. L; S. Harding; W. Juzytsch; D. Funk; Y. Shaham (Psychopharmacology, 2005)

Population structure of Columbia spotted frogs ( Rana luteiventris ) is strongly affected by the landscape - W. CHRIS FUNK; MICHAEL S. BLOUIN; PAUL STEPHEN CORN; BRYCE A. MAXELL; DAVID S. PILLIOD; STEPHEN AMISH; FRED W. ALLENDORF (Molecular Ecology, 2005)
Landscape features such as mountains, rivers, and ecological gradients may strongly affect patterns of dispersal and gene flow among populations and thereby shape population dynamics and evolutionary trajectories. The landscape may have a particularly strong effect on patterns of dispersal and gene flow in amphibians because amphibians are thought to have poor dispersal abilities. We examined genetic variation at six microsatellite loci in Columbia spotted frogs ( Rana luteiventris ) from 28 breeding ponds in western Montana and Idaho, USA, in order to investigate the effects of landscape structure on patterns of gene flow. We were particularly interested in addressing three questions: (i) do ridges act as barriers to gene flow? (ii) is gene flow restricted between low and high elevation ponds? (iii) does a pond equal a ‘randomly mating population’ (a deme)? We found that mountain ridges and elevational differences were associated with increased genetic differentiation among sites, suggesting that gene flow is restricted by ridges and elevation in this species. We also found that populations of Columbia spotted frogs generally include more than a single pond except for very isolated ponds. There was also evidence for surprisingly high levels of gene flow among low elevation sites separated by large distances. Moreover, genetic variation within populations was strongly negatively correlated with elevation, suggesting effective population sizes are much smaller at high elevation than at low elevation. Our results show that landscape features have a profound effect on patterns of genetic variation in Columbia spotted frogs.

Influence of stressors on the rewarding effects of alcohol in Wistar rats: studies with alcohol deprivation and place conditioning - D. Funk; S. Vohra; A. D. L (Psychopharmacology, 2004)

Transformation of triploid bermudagrass (Cynodon dactylon x C. transvaalensis cv. TifEagle) by means of biolistic bombardment - G. Zhang; S. Lu; T. A. Chen; C. R. Funk; W. A. Meyer (Plant Cell Reports, 2003)

Patterns of nuclear DNA degeneration over time — a case study in historic teeth samples - P. Wandeler; S. Smith; P. A. Morin; R. A. Pettifor; S. M. Funk (Molecular Ecology, 2003)
The amount of nuclear DNA extracted from teeth of 279 individual red fox Vulpes vulpes collected over a period spanning the last three decades was determined by quantitative polymerase chain reaction (PCR). Although teeth were autoclaved during initial collection, 73.8% of extracts contained sufficient DNA concentration (> 5 pg/µL) suitable for reliable microsatellite genotyping but the quantity of nuclear DNA decayed significantly over time in a nonlinear pattern. The success of PCR amplification across four examined canine microsatellites over time was dependent on fragment size. By including data from two different tests for human contamination and from frequencies of allelic dropout and false alleles, the methodological constraints of population genetic studies using microsatellite loci amplified from historic DNA are discussed.

The city‐fox phenomenon: genetic consequences of a recent colonization of urban habitat - P. Wandeler; S. M. Funk; C. R. Largiadèr; S. Gloor; U. Breitenmoser (Molecular Ecology, 2003)
The red fox ( Vulpes vulpes ) is one of the best‐documented examples of a species that has successfully occupied cities and their suburbs during the last century. The city of Zurich (Switzerland) was colonized by red foxes 15 years ago and the number of recorded individuals has increased steadily since then. Here, we assessed the hypothesis that the fox population within the city of Zurich is isolated from adjacent rural fox populations against the alternative hypothesis that urban habitat acts as a constant sink for rural dispersers. We examined 11 microsatellite loci in 128 foxes from two urban areas, separated by the main river crossing the city, and three adjacent rural areas from the region of Zurich. Mean observed heterozygosity across individuals and the number of detected alleles were lower for foxes collected within the city as compared with their rural conspecifics. Genetic differentiation was significantly lower between rural than between rural and urban populations, and highest value of pairwise F ST was recorded between the two urban areas. Our results indicate that the two urban areas were independently founded by a small number of individuals from adjacent rural areas resulting in genetic drift and genetic differentiation between rural and urban fox populations. Population admixture and immigration analysis revealed that urban–rural gene flow was higher than expected from F ST statistics. In the five to seven generations since colonization, fox density has dramatically increased. Currently observed levels of migration between urban and rural populations will probably erode genetic differentiation over time.

Amino acid deletions in the cytosolic domains of the chlorophyll a-binding protein CP47 slow QA − oxidation and/or prevent the assembly of Photosystem II - Shannon M. Clarke; Christiane Funk; Garth S. Hendry; Jackie A. Shand; Tom Wydrzynski; Julian J. Eaton-Rye (Plant Molecular Biology, 2002)